2022
DOI: 10.1210/endocr/bqac206
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth and Corticotrophin-Releasing Hormone as a Placental Clock

Abstract: Preterm birth worldwide remains a significant cause of neonatal morbidity and mortality. Yet the exact mechanisms of preterm parturition remain unclear. Preterm birth is not a single condition, but rather a syndrome with a multifactorial etiology. This multifactorial nature explains why individual predictive measures for preterm birth have had limited sensitivity and specificity. One proposed pathway for preterm birth is via placentally synthesized corticotrophin-releasing hormone (CRH). CRH is a peptide hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…By activating the embryonic HPA axis, placental CRH may initiate labor. Elevated placental CRH concentrations have been linked to preterm labor [ 17 , 18 ]. Furthermore, preterm fetuses have higher plasma EPI concentrations than term fetuses [ 19 ].…”
Section: Maternal Stress and Birth Outcomesmentioning
confidence: 99%
“…By activating the embryonic HPA axis, placental CRH may initiate labor. Elevated placental CRH concentrations have been linked to preterm labor [ 17 , 18 ]. Furthermore, preterm fetuses have higher plasma EPI concentrations than term fetuses [ 19 ].…”
Section: Maternal Stress and Birth Outcomesmentioning
confidence: 99%
“…10,11 In addition, cold-stress may trigger the release of placental corticotropin-releasing hormone, a key factor in initiating human parturition. 12 Conversely, high temperatures can cause dehydration, leading to reduced uterine blood flow and increased secretion of antidiuretic hormone and oxytocin, which could induce labour. 13 While recent systematic reviews have indicated possible associations between low-and high-temperature exposures and increased PTB risks, they have also reported inconsistencies in the findings across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Low temperatures may induce increased blood viscosity and vascular constriction, 9 ultimately impairing uteroplacental blood flow and potentially resulting in PTB 10,11 . In addition, cold‐stress may trigger the release of placental corticotropin‐releasing hormone, a key factor in initiating human parturition 12 . Conversely, high temperatures can cause dehydration, leading to reduced uterine blood flow and increased secretion of antidiuretic hormone and oxytocin, which could induce labour 13 …”
Section: Introductionmentioning
confidence: 99%